Incentives work: performance-related remuneration of directors before and during the great depression in Belgium. (10th September 2018) - Vermoesen, Veronique; Deloof, Marc; Schwienbacher, Armin
Abstract: We study the payment of bonuses to directors of Belgian firms listed on the Brussels Stock Exchange in 1925–1934. Directors received substantial cash bonuses which were positively related to firm performance, measured by accounting income and changes in the market value of equity. If shareholders were expropriated via the payment of excessive director bonuses, we would expect a larger drop in stock market performance during the Great Depression for firms paying higher bonuses. However, our findings suggest that bonuses were a valuable tool for aligning the interest of directors and shareholders in an environment characterized by weak legal investor protection.